In situ synchrotron X‐ray diffraction investigation of the evolution of a PbO2/PbSO4 surface layer on a copper electrowinning Pb anode in a novel electrochemical flow cell. (3rd February 2015) - Clancy, Marie; Styles, Mark J.; Bettles, Colleen J.; Birbilis, Nick; Chen, Miao; Zhang, Yansheng; Gu, Qinfen; Kimpton, Justin A.; Webster, Nathan A. S.
<x xml:space="preserve">Abstract</x> This paper describes the quantitative measurement, by in situ synchrotron X‐ray diffraction (S‐XRD) and subsequent Rietveld‐based quantitative phase analysis and thickness calculations, of the evolution of the PbO2 and PbSO4 surface layers formed on a pure lead anode under simulated copper electrowinning conditions in a 1.6 M H2SO4 electrolyte at 318 K. This is the first report of a truly in situ S‐XRD study of the surface layer evolution on a Pb substrate under cycles of galvanostatic and power interruption conditions, of key interest to the mining, solvent extraction and lead acid battery communities. The design of a novel reflection geometry electrochemical flow cell is also described. The in situ S‐XRD results show that β‐PbO2 forms immediately on the anode under galvanostatic conditions, and undergoes continued growth until power interruption where it transforms to PbSO4. The kinetics of the β‐PbO2 to PbSO4 conversion decrease as the number of cycles increases, whilst the amount of residual PbO2 increases with the number of cycles due to incomplete conversion to PbSO4. Conversely, complete transformation of PbSO4 to β‐PbO2 was observed in each cycle. The results of layer thickness calculations demonstrate a significant volume change upon PbSO4 to β‐PbO2 transformation.